Evidence for a genetic link between bone and vascular measures in African ancestry families. (18th July 2013) - Kuipers, Allison L; Miljkovic, Iva; Kammerer, Candace M; Evans, Rhobert W; Bunker, Clareann H; Patrick, Alan L; Wheeler, Victor W; Sutton‐Tyrrell, Kim; Zmuda, Joseph M
Abstract: Bone mineral density (BMD) has been inversely associated with subclinical and clinical cardiovascular disease (CVD) in population studies, but the potential mechanisms underlying this relationship are unclear. To test if there is a genetic basis underlying this association, we determined the phenotypic and genetic correlations between BMD and carotid artery ultrasound measures in families. Dual‐energy X‐ray absorptiometry and peripheral quantitative computed tomography were used to measure BMD in 461 individuals with African ancestry belonging to seven large, multigenerational families (mean family size 66; 3414 total relative pairs). Carotid artery ultrasound was used to measure adventitial diameter (AD) and intima‐media thickness (IMT). Phenotypic and genetic correlations between BMD and carotid measures were determined using pedigree‐based maximum likelihood methods. We adjusted for potential confounding factors, including age, sex, body weight, height, menopausal status, smoking, alcohol intake, walking for exercise, diabetes, hypertension, serum lipid and lipoprotein levels, inflammation markers, and kidney function. We found statistically significant phenotypic (ρ = − 0.19) and genetic (ρG  = − 0.70) correlations ( p  < 0.05 for both) between lumbar spine BMD and AD in fully adjusted models. There was also a significant genetic correlation between trabecular BMD at the radius and IMT in fully adjusted models (ρG  = − 0.398; p  < 0.05). Our findings indicate that the previously observed association between osteoporosis and CVD in population‐based studies may be partly mediated by genetic factors and that the pleiotropic effects of these genes may operate independently of traditional risk pathways.